(untitled) (Revista Apotheke, 2022)
This paper presents the final results of the research named Mediated objects: miscegenated paintings, which was developed between 2011 and 2013, and it is characterized by presenting an investigation that was established by the combination of artistic practices and theoretical reflections that deal with poetic strategies adopted by the conception and realization of those works. The proposal is based on contemporary issues that cover the representation of objects in painting (still life) through the use of technical image, pictorial process that relates the concept of miscegenation. It was possible to identify in those poetic strategies that the questions moved from the objects to the noise through mediated technique (optic) of the model.